Pressure-compacted and spider silk–reinforced fibrin demonstrates sufficient biomechanical stability as cardiac patch in vitro. (January 2022) - Bobylev, Dmitry; Wilhelmi, Mathias; Lau, Skadi; Klingenberg, Melanie; Mlinaric, Markus; Petená, Elena; Helms, Florian; Hassel, Thomas; Haverich, Axel; Horke, Alexander; Böer, Ulrike
Objective: The generation of bio-/hemocompatible cardiovascular patches with sufficient stability and regenerative potential remains an unmet goal. Thus, the aim of this study was the generation and in vitro biomechanical evaluation of a novel cardiovascular patch composed of pressure-compacted fibrin with embedded spider silk cocoons. Methods: Fibrin-based patches were cast in a customized circular mold. One cocoon of Nephila odulis spider silk was embedded per patch during the casting process. After polymerization, the fibrin clot was compacted by 2 kg weight for 30 min resulting in thickness reduction from up to 2 cm to <1 mm. Tensile strength and burst pressure was determined after 0 weeks and 14 weeks of storage. A sewing strength test and a long-term load test were performed using a customized device to exert physiological pulsatile stretching of a silicon surface on which the patch had been sutured. Results: Fibrin patches resisted supraphysiological pressures of well over 2000 mmHg. Embedding of spider silk increased tensile force 1.8-fold and tensile strength 1.45-fold ( p < .001), resulting in a final strength of 1.07 MPa and increased sewing strength. Storage for 14 weeks decreased tensile strength, but not significantly and suturing properties of the spider silk patches were satisfactory. The long-term load test indicated that the patches were stable for 4 weeks although slight reduction in patch material was observed. Conclusion: The combination of compacted fibrin matrices and spider silk cocoons may represent a feasible concept to generate stable and biocompatible cardiovascular patches with regenerative potential.